The Relationship Between Cognitive Processes and Language Production in Foreign Language Learners - Sofiyani Nasution; Huda Hizkia Ahmad; Nadila Tanjung; Yani Lubis (Lembaga Pengembangan Kinerja Dosen, 2024)
This study explores the relationship between cognitive processes and language production among foreign language learners by analyzing the roles of working memory, attentional control, and self-monitoring in shaping spoken and written performance. Employing a qualitative descriptive design, data were gathered through semi-structured interviews, task-based classroom observations, and analysis of learners’ written outputs. The findings indicate that cognitive mechanisms significantly influence the fluency, accuracy, and complexity of learners’ language production. Learners with stronger working memory capacity demonstrated better ability to integrate information, construct coherent sentences, and maintain linguistic accuracy, while those with limited memory resources tended to rely on simplification strategies and reduced syntactic complexity. Attentional control was found to be crucial in managing competing linguistic demands, especially during spontaneous speech. Additionally, self-monitoring contributed to improved error correction and refinement of ideas, particularly in writing tasks, where learners have more time for cognitive planning compared to spoken communication. Differences between oral and written performance further highlight how task modality interacts with cognitive load. Overall, the study emphasizes that cognitive functioning plays a pivotal role in determining learners’ language output, and suggests that instructional practices aimed at strengthening cognitive skills may enhance communicative competence in foreign language learning contexts.